Wpływ miejscowych analogów prostaglandyn na rogówkę – doniesienie wstępne - Wierzbowska, Joanna; Stankiewicz, Andrzej (Klinika Oczna / Acta Ophthalmologica Polonica, 2006)
In the article the recent research on the biology of corneal stroma and biological impact of topical prostaglandin analogues on this tissue, were presented. The outcome of some studies, regarding influence of this class of antiglaucoma medication on central corneal thickness (CCT), were included. The impact of CCT on the readings of intraocular pressure and the aspect of diurnal fluctuations of CCT were also emphasized.